Evangelical Youth Culture: Alternative Music and Extreme Sports Subcultures - Abraham, Ibrahim (Bloomsbury Publishing PLC, 2017)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Acknowledgments -- Introduction -- Contextualizing Evangelical youth culture -- Studying Evangelical youth cultures -- 1 Evangelical Christianity and Youth Subculture Theory -- Introduction -- Christianity as counterculture and counter-counterculture -- Secular youth subcultures -- The post-subcultural turn -- Evangelical subcultures -- Conclusion -- 2 Christian Punk in an Age of Authenticity -- Introduction -- A brief history of Christian punk -- Authenticity between the sacred and the secular -- Authenticity in secular popular music -- Authenticity in contemporary Christian music -- Evangelical authenticity in secular punk culture -- Punk authenticity in Evangelical youth culture -- Conclusion -- 3 Postsecular Punk: Christianity's Contested Inclusion in Alternative Music Scenes -- Introduction -- Theorizing punk's postsecular turn -- Theorizing punk's overlapping consensus -- Enacting punk's overlapping consensus -- Undermining punk's overlapping consensus -- Respectful relationships and religious conflict in alternative music scenes -- Conclusion -- 4 Evangelical Extreme Sports Subcultures and Youth Development Ministry -- Introduction -- Extreme sports spirituality and culture -- Extreme sports evangelism -- Negotiating Evangelical ecclesial norms -- Evangelical extreme sports-based youth development -- Conclusion -- 5 Serious Leisure and Salvation Anxiety in Evangelical Youth Culture -- Introduction -- The serious leisure perspective -- Serious leisure and Evangelical youth culture -- Salvation anxiety in Evangelical youth culture -- Rituals of rupture in Evangelical youth culture -- Sacralizing serious leisure in Evangelical youth culture -- Conclusion -- 6 Fear of a Black Magic: Evangelical Opposition to Alternative Youth Culture -- Introduction